Analysis of 31 Hydrazones of Carbonyl Compounds by RRLC-UV and RRLC-MS(/MS): A Comparison of Methods - Soraya de M. Ochs; Maíra Fasciotti; Annibal D. Pereira Netto (Journal of Spectroscopy)
Aldehydes and ketones are volatile organic compounds (VOC) emitted into the atmosphere by a large number of natural and anthropogenic sources. Carbonyl compounds (CC) are atmospheric pollutants with known damaging effects for the human’s health. In this work, the separation of 31 carbonyl compounds (CC) in their 2,4-dinitrophenylhydrazones form was optimized by rapid resolution liquid chromatography in 9 minutes and simultaneously detected by ultraviolet and mass spectrometry with an APCI(−) as ionization source. The mass spectra of hydrazones presented the [M-H]− ions as base peak, but the MS/MS spectra showed fragments related to different structural classes of aldehydes and ketones, representing an important tool to assist structure elucidation of unknown CC in real samples. Multiple reactions monitoring (MRM) improved the sensitivity and selectivity for the quantitation method. Analytical parameters using both UV and MS (linearity, determination coefficients, detection limits, and sensitivity) were compared. The detection methods are complementary and a powerful analytical tool for the detection and quantitation of CC in complex environmental samples.